Deskripsi Kepercayaan Konsumen, Risiko, dan Kualitas Produk Berdasarkan Ulasan Konsumen Tahun 2024 - 2025 di Marketplace Shopee Toko Pelangi Nicer - Sianturi, Winan Sutomo (Lembaga Yasin AlSys, 2026)
The development of e-commerce has increasingly encouraged consumers to rely on reviews to assess trust, risk, and product quality before making a purchase. However, the information contained in reviews does not always accurately reflect the actual condition of products, thereby potentially influencing consumers’ purchasing decisions. This study aimed to describe consumer trust, perceived risk, and product quality based on consumer reviews of Pelangi Nicer Store on the Shopee marketplace during the 2024–2025 period. The study employed a qualitative descriptive approach supported by simple quantitative analysis using a content analysis design. The research data comprised 366 consumer reviews selected through purposive sampling from a population of 500 reviews. Data were collected through documentation, selection, coding, and classification of reviews and were subsequently analyzed using ChatGPT-assisted content analysis, which was reverified by the researcher through calculations of frequencies, percentages, and mean values. The results showed that consumer trust was categorized as poor because of the seller’s low integrity and unethical behavior, although the store’s reputation was considered relatively high. Consumers’ perceived risk was categorized as very high, particularly in relation to product, psychological, and delivery risks. Product quality was also categorized as poor because of low product durability, although its visual appearance was considered attractive. This study concludes that discrepancies between product descriptions and the actual condition of the products received are the primary factors that reduce consumer trust and increase perceived risk. These findings imply the importance of improving quality control, product information transparency, and seller service management to build consumer trust and enhance the store’s competitiveness in the marketplace.